2010
DOI: 10.1037/a0018092
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity and interpersonal competencies: Contrasting White and African American men.

Abstract: Masculinity ideologies inform expectations for how men should behave, and one important realm of behavior is that of interpersonal relationships. Conforming to Western-defined traditional male role norms has been linked to numerous aspects of relational health and functioning. However, as masculinity ideologies reflect the internalization of cultural beliefs and attitudes about men's roles, the associations between masculine ideologies and interpersonal functioning could differ by racial cultural group. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 43 publications
4
31
0
7
Order By: Relevance
“…Thus, responding to stressful situations and mental health issues can be a mysterious process for young men whose role models conform to traditional gender roles. The endorsement of traditional gender norms by black men compared with non-black men is consistent across studies (Courtenay 2000; Lease et al 2010; Levant et al 1998), and African American men tend to endorse more traditional perspective when compared with European American men (Courtenay 2000; Levant and Majors 1997; Levant et al 1998). The endorsement of traditional norms of masculinity also changes depending on the age and professional or non-professional status of men.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, responding to stressful situations and mental health issues can be a mysterious process for young men whose role models conform to traditional gender roles. The endorsement of traditional gender norms by black men compared with non-black men is consistent across studies (Courtenay 2000; Lease et al 2010; Levant et al 1998), and African American men tend to endorse more traditional perspective when compared with European American men (Courtenay 2000; Levant and Majors 1997; Levant et al 1998). The endorsement of traditional norms of masculinity also changes depending on the age and professional or non-professional status of men.…”
Section: Introductionsupporting
confidence: 62%
“…In recent years, studies on masculinity and mental health have identified complex, multifaceted impressions of what it means to be a man (Addis and Mahalik 2003; Brooks 2001; Harland 2008). Yet, additional complexities surface when attempting to understand how men are conditioned to embody manhood across different racial and ethnic groups (Hurtado and Sinha 2008; Lease et al 2010; Mahalik et al 2006; Royster 2007; Wester 2008) and how exposure to father figures in their youth influence their mental health outcomes in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings have shown that African American men score higher than members of other racial/ethnic groups, especially Caucasians, on measures of masculinity [8,9] and that Caucasian and African American men define masculinity differently [10]. When applied to situations involving sexual behavior, men who score higher on masculinity have been shown to be more likely to engage in HIV sexual risk behaviors compared to their less-masculine counterparts [1113].…”
Section: Introductionmentioning
confidence: 99%
“…Although the endorsement of such roles may vary between groups of men, studies have found that this view on masculinity is generally true cross-culturally and in numerous countries (Lease et al, 2010; Ojeda, Rosales, & Good, 2008). Consequently, if a man has internalized traditional messages regarding masculinity, then his psychological well-being may hinge on his ability to fulfill those roles (Glass & Owen, 2010; Rochlen, McKelley, Suizzo, & Scaringi, 2008).…”
Section: Social Class Status and Masculinitymentioning
confidence: 99%